The Reading Motivation and Reading Strategies Used by Undergraduates in University Teknologi MARA Dungun, Terengganu - Yah Awg Nik; Badariah Sani; Muhmad Noor Wan Chik; Nor Adeena Raslee (2011)
There is a major concern among educators and parents about children who cannot read but more seriously about those who can read but do not have the motivation to read. The study investigated 245 undergraduates’ level of reading motivation and their reading strategies use when they read academic texts. This study aims at finding the connection between reading motivation and reading strategy, to discover the differences between male and female students’ reading motivation and reading strategy and the relationship between variables such as program of study and family’s income. The results showed that the undergraduates’ reading motivation was of moderate level and they mostly use the cognitive reading strategy instead of the metacognitive reading strategy. There seemed to be a connection between the undergraduates’ reading motivation and the reading strategy used. The results indicated that the undergraduates’ motivation to read had an influence on the use of the reading strategy. Though female students had higher reading motivation compared to male students, both groups only use the cognitive reading strategy. Therefore, the results showed that undergraduates having moderate reading motivation tend to use only cognitive reading strategy. Thus, reading motivation does influence the acquisition of reading skills and there is a possibility that the higher reading motivation, the higher the tendency to use high level reading skills such as metacognitive which is a necessity for students’ effective reading. Instructors should motivate students to become active readers by improving students’ intrinsic motivation and decreasing their extrinsic motivation. Other results revealed that there was a significant difference among the five Diploma programs and finally, the students’ reading motivation had no significant relationship with their economic background.